The role of music in improving English language development among kindergarden student in Shah Alam / Izzatul Farha Abdul Latif - Abdul Latif, Izzatul Farha (2012)
This study is aimed at investigating the role of music in improving the development of English Language among kindergarten students. In doing so, eight teachers from four different schools were selected as the subjects of this research. The schools were Brainy Bunch Islamic Montessori Kindergarten, Section 3, Shah Alam , D’zul Iman Smart Khalifah Kindergarten, Section 9, Shah Alam , Sri Cahaya Kindergarten, Section 7, Shah Alam and Permata PKPS Kindergarten, Section 2, Shah Alam . Separate interview s were done in order to obtain the data needed. The teachers have provided significant perceptions on role of music in the development of English Language among kindergarten students. The usage of music in English lessons has a positive impact on students.